Polymer fluorinated gel electrolyte
By using polymer gel electrolytes containing sulfur and fluorine, boron, fluorinated plasticizers and non-fluorinated plasticizers, the room temperature rate performance, low temperature discharge and high temperature durability of solid-state battery packs is solved by using lithium salts of sulfur and fluorinated lithium salts, lithium salts of boron, fluorinated plasticizers, and non-fluorinated plasticizers. Inadequate aspects have achieved better battery pack performance.
Patent Information
- Application Number
- CN202311041393.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2025-02-21
AI Technical Summary
The existing solid-state battery packs have poor performance in room temperature magnification performance, low-temperature discharge and high-temperature durability, mainly due to the poor compatibility between conventional gel polymer electrolytes and the anode, resulting in the adverse formation of the solid electrolyte interface (SEI) layer.
The polymer gel electrolyte using a polymer gel that contains sulfur and fluorine, a lithium salt containing boron, a fluorinated plasticizer, a non-fluorinated plasticizer and a polymer body. The weight ratio is 9:1 to 1:9 to improve the performance of the electrolyte.
The polymer gel electrolyte significantly improves the room temperature magnification performance, low temperature discharge and high temperature durability of the battery pack, improving the performance of the battery pack in all climates.
Smart Images

Figure CN119495809A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to batteries, such as solid-state batteries, comprising polymer gel electrolytes having improved room temperature rate capability, low temperature discharge, and high temperature durability, and methods of forming the same. Background Art
[0002] Electrochemical energy storage devices, such as lithium-ion batteries, can be used in a variety of products, including automotive products, such as start-stop systems (e.g., 12V start-stop systems), battery-assisted systems ("μBAS"), hybrid electric vehicles ("HEV"), and electric vehicles ("EV"). A typical lithium-ion battery includes two electrodes and an electrolyte assembly and / or a separator. One of the two electrodes may serve as a positive electrode or cathode, and the other electrode may serve as a negative electrode or cathode. The lithium-ion battery may also include various terminals and packaging materials. Rechargeable lithium-ion batteries operate by reversibly transferring lithium ions back and forth between a negative electrode and a positive electrode. For example, lithium ions may move from a positive electrode to a negative electrode during charging of the battery and move in the opposite direction when the battery is discharged. A separator and / or electrolyte layer may be disposed between the negative electrode and the positive electrode. The electrolyte is suitable for conducting lithium ions between the electrodes, and it may be in solid form, liquid form, or a solid-liquid hybrid form like the two electrodes. In the case of a solid-state battery including a solid electrolyte layer disposed between solid electrodes, the solid electrolyte may physically separate the solid electrodes so that a separate separator is not required.
[0003] Solid-state batteries have advantages over batteries containing separators and liquid electrolytes. These advantages may include longer shelf life, lower self-discharge, simpler thermal management, reduced packaging requirements, and the ability to operate in a wider temperature window. For example, solid electrolytes are generally non-flammable, allowing batteries to circulate under more severe conditions without experiencing potential reduction or thermal runaway that may occur when using liquid electrolytes. In addition, in solid-state batteries, the interface contact between solid electrolyte particles and electrode active material particles may be poor. Introducing gel polymer electrolytes into solid-state batteries can help establish favorable lithium ion conduction at the interface. However, conventional gel polymer electrolytes for solid-state batteries may help form an unfavorable solid electrolyte interface (SEI) layer on the anode (e.g., graphite or silicon anode), thereby inhibiting the insertion and extraction of lithium ions. Due to the poor compatibility between the gel polymer electrolyte and the anode, batteries using such gel polymer electrolytes may experience poor performance within a certain temperature range, such as poor room temperature rate performance, poor low temperature discharge, and poor high temperature durability.
[0004] Therefore, it is desirable to provide a gel polymer electrolyte for high performance batteries that improves room temperature rate capability, low temperature discharge, and high temperature durability to improve battery performance in all climates. Summary of the invention
[0005] In an exemplary embodiment, the present disclosure provides a polymer gel electrolyte for an electrochemical cell. The polymer gel electrolyte includes a lithium salt containing sulfur and fluorine, a lithium salt containing boron, a fluorinated plasticizer, a non-fluorinated plasticizer, and a polymer host. The weight (w / w) ratio of the fluorinated plasticizer to the non-fluorinated plasticizer is 9:1 to 1:9.
[0006] In addition to one or more of the features described herein, the polymer gel electrolyte may satisfy one or more of the following: (i) the combination of the lithium salt containing sulfur and fluorine and the lithium salt containing boron may have a concentration of greater than or equal to about 1 molar (M) to less than or equal to about 4 M; and (ii) the lithium salt containing sulfur and fluorine and the lithium salt containing boron each have a concentration of greater than or equal to about 0.6 M to less than or equal to about 2 M.
[0007] In another exemplary embodiment, the lithium salt containing sulfur and fluorine may include a lithium cation (Li + ) and selected from bis-trifluoromethanesulfonimide (TFSI - ), bis(fluorosulfonyl)imide (FSI - ), trifluoromethanesulfonate - ), bis(pentafluoroethanesulfonyl)imide (BETI - ), cyclo-difluoromethane-1,1-bis(sulfonyl)imide (DMSI - ), cyclo-hexafluoropropane-1,1-bis(sulfonyl)imide (HPSI - ) and anions of combinations thereof; and lithium salts containing boron may include lithium cations (Li + ) and selected from tetrafluoroborate (BF4 - ), bis(oxalato)borate (BOB - ), tetracyanoborate (bison - ), difluoro(oxalate)borate (DFOB - ), bis(fluoromalonate)borate (BFMB - ) and anions of their combinations.
[0008] In yet another exemplary embodiment, the fluorinated plasticizer may include fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoropropylene carbonate (TFPC), methyl 2,2,2-trifluoroethyl carbonate, ethyl 2,2,2-trifluoroethyl carbonate, 2,2-difluoroethyl methyl carbonate, 2,2-difluoroethyl ethyl carbonate, 2,2-difluoroethyl acetate, 2,2,2-trifluoroethyl acetate, 1,1,2,2-tetrafluoroethyl 2,2, 3,3-tetrafluoropropyl ether or a combination thereof; and the non-fluorinated plasticizer may include γ-butyrolactone (GBL), propylene carbonate (PC), glycerol carbonate, vinylene carbonate, 1,2-butylene carbonate, δ-valerolactone, succinonitrile, glutaronitrile, adiponitrile, tetramethylene sulfone, ethyl methyl sulfone, vinyl sulfone, phenyl sulfone, benzyl sulfone, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dimethoxypropane, 1,4-dioxane, triethyl phosphate, trimethyl phosphate or a combination thereof.
[0009] In yet another exemplary embodiment, the lithium salt containing sulfur and fluorine may include lithium bis(trifluoromethanesulfonyl)imide (LiTFSI); the lithium salt containing boron may include lithium tetrafluoroborate (LiBF4); the fluorinated plasticizer may include fluoroethylene carbonate (FEC); the non-fluorinated plasticizer may include γ-butyrolactone (GBL); and the polymer host may include polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0010] In another exemplary embodiment, the polymer host can be selected from: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), poly(acrylic acid) (PAA), polypropylene oxide (PPO), polyacrylonitrile (PAN), polymethacrylonitrile (PMAN), polymethyl methacrylate (PMMA), carboxymethyl cellulose (CMC), poly(vinyl alcohol) (PVA), polyvinyl pyrrolidone (PVP) and combinations thereof.
[0011] In another exemplary embodiment, the polymer gel electrolyte can satisfy one or more of the following: (i) a combination of a lithium salt comprising sulfur and fluorine and a lithium salt comprising boron can have a concentration greater than or equal to about 1.2 M to less than or equal to about 4 M; (ii) the lithium salt comprising sulfur and fluorine and the lithium salt comprising boron each have a concentration greater than or equal to about 0.6 M to less than or equal to about 2 M; (iii) the w / w ratio of the fluorinated plasticizer to the non-fluorinated plasticizer is from about 0.9:1 w / w to about 0.2:1 w / w; and (iv) the polymer host is present in an amount of 0.5 weight percent (wt %) to about 40 wt %.
[0012] In yet another exemplary embodiment, the polymer gel electrolyte may meet one or more of the following: (i) the lithium salt containing sulfur and fluorine may include lithium bis(trifluoromethanesulfonyl)imide (LiTFSI); (ii) the lithium salt containing boron may include lithium tetrafluoroborate (LiBF4); (iii) the fluorinated plasticizer may include fluoroethylene carbonate (FEC); (iv) the non-fluorinated plasticizer may include γ-butyrolactone (GBL); and (v) the polymer matrix may include poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP).
[0013] In yet another exemplary embodiment, the polymer gel electrolyte may further include solid electrolyte particles.
[0014] In one exemplary embodiment, the present disclosure provides an electrochemical cell. The electrochemical cell includes a first electrode comprising a first electroactive material, a second electrode comprising a second electroactive material, and an electrolyte layer disposed between the first electrode and the second electrode. At least one of the first electrode, the second electrode, and the electrolyte layer may include a polymer gel electrolyte. The polymer gel electrolyte includes a lithium salt containing sulfur and fluorine, a lithium salt containing boron, a fluorinated plasticizer, a non-fluorinated plasticizer, and a polymer matrix. The w / w ratio of the fluorinated plasticizer to the non-fluorinated plasticizer is from 9:1 to 1:9.
[0015] In addition to one or more features described herein, the electrolyte layer may include a plurality of solid electrolyte particles and a polymer gel electrolyte at least partially filling the void spaces between the solid electrolyte particles.
[0016] In another exemplary embodiment, the electrolyte layer may further include a separator, wherein the gel polymer electrolyte at least partially fills the void spaces in the polymer separator.
[0017] In yet another exemplary embodiment, the first electroactive material may be selected from Li (1+x) Mn2O4, where 0.1 ≤ x ≤ 1; LiMn (2-x) Ni x O4, where 0 ≤ x ≤ 0.5; LiCoO2; Li(Ni x Mn y Co z )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤, 0 ≤ z ≤ 1 and x + y + z = 1; LiNi (1-x-y) Co x M y O2, where 0 < x < 0.2, y < 0.2 and M is Al, Mg or Ti; LiFePO4, LiMn 2- x Fe xPO4, where 0 < x < 0.3; LiNiCoAlO2; LiMPO4, where M is at least one of Fe, Ni, Co, and Mn; Li(Ni x Mn y Co z Al p )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ p ≤ 1, and x + y + z + p = 1 (NCMA); LiNiMnCoO2; Li2Fe x M 1-x PO4, where M is Mn and / or Ni, 0 ≤ x ≤ 1; LiMn2O4 (LMO); LiFeSiO4; LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622), LiMnO2, LiNi 0.5 , Mn 1.5 O4, LiV2(PO4)3, activated carbon, sulfur, and combinations thereof. The second electroactive material may include metallic lithium, lithium alloys, silicon, graphite, activated carbon, carbon black, hard carbon, soft carbon, graphene, tin oxide, aluminum, indium, zinc, germanium, silicon oxide, titanium oxide, lithium titanate, iron sulfide (FeS), Li4Ti5O 12 or combinations thereof.
[0018] In yet another exemplary embodiment, the polymeric gel electrolyte may satisfy one or more of the following: (i) a combination of a lithium salt containing sulfur and fluorine and a lithium salt containing boron may have a concentration greater than or equal to about 1 M to less than or equal to about 4 M; and (ii) the lithium salt containing sulfur and fluorine and the lithium salt containing boron each have a concentration greater than or equal to about 0.6 M to less than or equal to about 2 M.
[0019] In yet another exemplary embodiment, the lithium salt containing sulfur and fluorine may include lithium cations (Li + ) and anions selected from bis-trifluoromethanesulfonylimide (TFSI - ), bis(fluorosulfonyl)imide (FSI - ), triflate - ), bis(pentafluoroethanesulfonyl)imide (BETI - ), cyclo-difluoromethane-1,1-bis(sulfonyl)imide (DMSI - ), cyclo-hexafluoropropane-1,1-bis(sulfonyl)imide (HPSI - ) and combinations thereof; and the lithium salt containing boron may include lithium cations (Li + ) and anions selected from tetrafluoroborate (BF4 - ), bis(oxalato)borate (BOB -), tetracyanoborate (bison - ), difluoro(oxalate)borate (DFOB - ), bis(fluoromalonate)borate (BFMB - ) and anions of their combinations.
[0020] In yet another exemplary embodiment, the fluorinated plasticizer may include fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoropropylene carbonate (TFPC), methyl 2,2,2-trifluoroethyl carbonate, ethyl 2,2,2-trifluoroethyl carbonate, 2,2-difluoroethyl methyl carbonate, 2,2-difluoroethyl ethyl carbonate, 2,2-difluoroethyl acetate, 2,2,2-trifluoroethyl acetate, 1,1,2,2-tetrafluoroethyl 2,2,3 ,3-tetrafluoropropyl ether or a combination thereof; and the non-fluorinated plasticizer may include γ-butyrolactone (GBL), propylene carbonate (PC), glycerol carbonate, vinylene carbonate, 1,2-butylene carbonate, δ-valerolactone, succinonitrile, glutaronitrile, adiponitrile, tetramethylene sulfone, ethyl methyl sulfone, vinyl sulfone, phenyl sulfone, benzyl sulfone, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dimethoxypropane, 1,4-dioxane, triethyl phosphate, trimethyl phosphate or a combination thereof.
[0021] In yet another exemplary embodiment, the lithium salt containing sulfur and fluorine may include lithium bis(trifluoromethanesulfonyl)imide (LiTFSI); the lithium salt containing boron may include lithium tetrafluoroborate (LiBF4); the fluorinated plasticizer may include fluoroethylene carbonate (FEC); the non-fluorinated plasticizer may include γ-butyrolactone (GBL); and the polymer host may include polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0022] In another exemplary embodiment, the polymer host can be selected from: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), poly(acrylic acid) (PAA), polypropylene oxide (PPO), polyacrylonitrile (PAN), polymethacrylonitrile (PMAN), polymethyl methacrylate (PMMA), carboxymethyl cellulose (CMC), poly(vinyl alcohol) (PVA), polyvinyl pyrrolidone (PVP) and combinations thereof.
[0023] In another exemplary embodiment, the polymer gel electrolyte may satisfy one or more of the following: (i) a combination of a lithium salt comprising sulfur and fluorine and a lithium salt comprising boron may have a concentration of greater than or equal to about 1.2 M to less than or equal to about 4 M; (ii) the lithium salt comprising sulfur and fluorine and the lithium salt comprising boron each have a concentration of greater than or equal to about 0.6 M to less than or equal to about 2 M; (iii) the w / w ratio of the fluorinated plasticizer to the non-fluorinated plasticizer is from about 0.9:1 w / w to about 0.2:1 w / w, and (iv) the polymer host is present in an amount of 0.5 wt % to about 40 wt %.
[0024] In yet another exemplary embodiment, the polymer gel electrolyte may satisfy one or more of the following: (i) the lithium salt containing sulfur and fluorine may include lithium bis(trifluoromethanesulfonyl)imide (LiTFSI); (ii) the lithium salt containing boron may include lithium tetrafluoroborate (LiBF4); (iii) the fluorinated plasticizer may include fluoroethylene carbonate (FEC); (iv) the non-fluorinated plasticizer may include γ-butyrolactone (GBL); and (v) the polymer host may include polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0025] The present disclosure also relates to the following embodiments:
[0026] 1. A polymer gel electrolyte for an electrochemical cell, wherein the polymer gel electrolyte comprises:
[0027] Lithium salts containing sulfur and fluorine;
[0028] Lithium salts containing boron;
[0029] Fluorinated plasticizers;
[0030] Non-fluorinated plasticizers; and
[0031] Polymer body,
[0032] The w / w ratio of the fluorinated plasticizer to the non-fluorinated plasticizer is from 9:1 to 1:9.
[0033] 2. The polymer gel electrolyte of embodiment 1, wherein the lithium salt containing sulfur and fluorine and the lithium salt containing boron each have a concentration of greater than or equal to about 0.6 M to less than or equal to about 2 M.
[0034] 3. The polymer gel electrolyte of embodiment 1, wherein:
[0035] The lithium salt containing sulfur and fluorine contains lithium cations (Li + ) and selected from bis-trifluoromethanesulfonimide (TFSI - ), bis(fluorosulfonyl)imide (FSI -), trifluoromethanesulfonate - ), bis(pentafluoroethanesulfonyl)imide (BETI - ), cyclo-difluoromethane-1,1-bis(sulfonyl)imide (DMSI - ), cyclo-hexafluoropropane-1,1-bis(sulfonyl)imide (HPSI - ) and combinations thereof; and
[0036] The boron-containing lithium salt comprises a lithium cation (Li + ) and selected from tetrafluoroborate (BF4 - ), bis(oxalato)borate (BOB - ), tetracyanoborate (bison - ), difluoro(oxalate)borate (DFOB - ), bis(fluoromalonate)borate (BFMB - ) and anions of their combinations.
[0037] 4. The polymer gel electrolyte of embodiment 1, wherein:
[0038] The fluorinated plasticizer comprises fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoropropylene carbonate (TFPC), methyl 2,2,2-trifluoroethyl carbonate, ethyl 2,2,2-trifluoroethyl carbonate, 2,2-difluoroethyl methyl carbonate, 2,2-difluoroethyl ethyl ethyl carbonate, 2,2-difluoroethyl acetate, 2,2,2-trifluoroethyl acetate, 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether or a combination thereof; and
[0039] The non-fluorinated plasticizer comprises gamma-butyrolactone (GBL), propylene carbonate (PC), glycerol carbonate, vinylene carbonate, 1,2-butylene carbonate, delta-valerolactone, succinonitrile, glutaronitrile, adiponitrile, tetramethylene sulfone, ethyl methyl sulfone, vinyl sulfone, phenyl sulfone, benzyl sulfone, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dimethoxypropane, 1,4-dioxane, triethyl phosphate, trimethyl phosphate or a combination thereof.
[0040] 5. The polymer gel electrolyte of embodiment 1, wherein:
[0041] The lithium salt comprising sulfur and fluorine comprises lithium bis(trifluoromethanesulfonyl)imide (LiTFSI);
[0042] The boron-containing lithium salt comprises lithium tetrafluoroborate (LiBF4);
[0043] The fluorinated plasticizer comprises fluoroethylene carbonate (FEC);
[0044] The non-fluorinated plasticizer comprises gamma-butyrolactone (GBL); and
[0045] The polymer host includes polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0046] 6. The polymer gel electrolyte described in embodiment 1, wherein the polymer host is selected from: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), poly(acrylic acid) (PAA), polypropylene oxide (PPO), polyacrylonitrile (PAN), polymethacrylonitrile (PMAN), polymethyl methacrylate (PMMA), carboxymethyl cellulose (CMC), poly(vinyl alcohol) (PVA), polyvinyl pyrrolidone (PVP) and combinations thereof.
[0047] 7. The polymer gel electrolyte of embodiment 1, wherein one or more of the following conditions are met:
[0048] (i) the combination of the lithium salt comprising sulfur and fluorine and the lithium salt comprising boron has a concentration of greater than or equal to about 1.2 M to less than or equal to about 4 M;
[0049] (ii) the lithium salt comprising sulfur and fluorine and the lithium salt comprising boron each have a concentration of greater than or equal to about 0.6 M to less than or equal to about 2 M;
[0050] (iii) a w / w ratio of the fluorinated plasticizer to the non-fluorinated plasticizer of from about 0.9:1 w / w to about 0.2:1 w / w; and
[0051] (iv) the polymer host is present in an amount of 0.5 wt % to about 40 wt %.
[0052] 8. The polymer gel electrolyte of embodiment 1, wherein one or more of the following conditions are met:
[0053] (i) the lithium salt comprising sulfur and fluorine comprises lithium bis(trifluoromethanesulfonyl)imide (LiTFSI);
[0054] (ii) the boron-containing lithium salt comprises lithium tetrafluoroborate (LiBF4);
[0055] (iii) the fluorinated plasticizer comprises fluoroethylene carbonate (FEC);
[0056] (iv) the non-fluorinated plasticizer comprises gamma-butyrolactone (GBL); and
[0057] (v) The polymer host comprises polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0058] 9. The polymer gel electrolyte according to Embodiment 1, further comprising solid electrolyte particles.
[0059] 10. An electrochemical cell for cycling lithium ions, the electrochemical cell comprising:
[0060] A first electrode comprising a first electroactive material;
[0061] A second electrode comprising a second electroactive material; and
[0062] An electrolyte layer disposed between the first electrode and the second electrode, wherein at least one of the first electrode, the second electrode, and the electrolyte layer comprises a polymer gel electrolyte, the polymer gel electrolyte comprising:
[0063] A lithium salt containing sulfur and fluorine;
[0064] A lithium salt containing boron;
[0065] A fluorinated plasticizer;
[0066] A non-fluorinated plasticizer; and
[0067] A polymer matrix.
[0068] 11. The electrochemical cell according to Embodiment 10, wherein the electrolyte layer comprises:
[0069] A plurality of solid electrolyte particles and the polymer gel electrolyte at least partially filling the void spaces between the solid electrolyte particles.
[0070] 12. The electrochemical cell according to Embodiment 10, wherein the electrolyte layer further comprises a separator, and the gel polymer electrolyte at least partially fills the void spaces in the separator.
[0071] 13. The electrochemical cell according to Embodiment 10, wherein:
[0072] The first electroactive material is selected from Li (1+x) Mn2O4, where 0.1 ≤ x ≤ 1; LiMn (2-x) Ni x O4, where 0 ≤ x ≤ 0.5; LiCoO2; Li(Ni x Mn y Co z )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤, 0 ≤ z ≤ 1 and x + y + z = 1; LiNi (1-x-y) Co x M y O2, where 0 < x < 0.2, y < 0.2 and M is Al, Mg or Ti; LiFePO4, LiMn2-x Fe x PO4, where 0 < x < 0.3; LiNiCoAlO2; LiMPO4, where M is at least one of Fe, Ni, Co, and Mn; Li(Ni x Mn y Co z Al p )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ p ≤ 1, x + y + z + p = 1 (NCMA); LiNiMnCoO2; Li2Fe x M 1-x PO4, where M is Mn and / or Ni, 0 ≤ x ≤ 1; LiMn2O4 (LMO); LiFeSiO4; LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622), LiMnO2, LiNi 0.5 , Mn 1.5 O4, LiV2(PO4)3, activated carbon, sulfur, and combinations thereof; and
[0073] The second electroactive material comprises metallic lithium, lithium alloy, silicon, graphite, activated carbon, carbon black, hard carbon, soft carbon, graphene, tin oxide, aluminum, indium, zinc, germanium, silicon oxide, titanium oxide, lithium titanate, iron sulfide (FeS), Li4Ti5O 12 or combinations thereof.
[0074] 14. The electrochemical cell according to embodiment 10, wherein one or more of the following are satisfied:
[0075] (i) The combination of the lithium salt containing sulfur and fluorine and the lithium salt containing boron has a concentration greater than or equal to about 1 M and less than or equal to about 4 M; and
[0076] (ii) The lithium salt containing sulfur and fluorine and the lithium salt containing boron each have a concentration greater than or equal to about 0.6 M and less than or equal to about 2 M.
[0077] 15. The electrochemical cell according to embodiment 10, wherein:
[0078] The lithium salt containing sulfur and fluorine comprises lithium cations (Li + ) and is selected from bis-trifluoromethanesulfonylimide (TFSI - ), bis(fluorosulfonyl)imide (FSI - ), triflate - ), bis(pentafluoroethanesulfonyl)imide (BETI - ), cyclo-difluoromethane-1,1-bis(sulfonyl)imide (DMSI -), cyclo-hexafluoropropane-1,1-bis(sulfonyl)imide (HPSI - ) and combinations thereof; and
[0079] The boron-containing lithium salt comprises a lithium cation (Li + ) and selected from tetrafluoroborate (BF4 - ), bis(oxalato)borate (BOB - ), tetracyanoborate (bison - ), difluoro(oxalate)borate (DFOB - ), bis(fluoromalonate)borate (BFMB - ) and anions of their combinations.
[0080] 16. The electrochemical cell of embodiment 10, wherein:
[0081] The fluorinated plasticizer comprises fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoropropylene carbonate (TFPC), methyl 2,2,2-trifluoroethyl carbonate, ethyl 2,2,2-trifluoroethyl carbonate, 2,2-difluoroethyl methyl carbonate, 2,2-difluoroethyl ethyl ethyl carbonate, 2,2-difluoroethyl acetate, 2,2,2-trifluoroethyl acetate, 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether or a combination thereof; and
[0082] The non-fluorinated plasticizer comprises gamma-butyrolactone (GBL), propylene carbonate (PC), glycerol carbonate, vinylene carbonate, 1,2-butylene carbonate, delta-valerolactone, succinonitrile, glutaronitrile, adiponitrile, tetramethylene sulfone, ethyl methyl sulfone, vinyl sulfone, phenyl sulfone, benzyl sulfone, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dimethoxypropane, 1,4-dioxane, triethyl phosphate, trimethyl phosphate or a combination thereof.
[0083] 17. The electrochemical cell of embodiment 10, wherein:
[0084] The lithium salt comprising sulfur and fluorine comprises lithium bis(trifluoromethanesulfonyl)imide (LiTFSI);
[0085] The boron-containing lithium salt comprises lithium tetrafluoroborate (LiBF4);
[0086] The fluorinated plasticizer comprises fluoroethylene carbonate (FEC);
[0087] The non-fluorinated plasticizer comprises gamma-butyrolactone (GBL); and
[0088] The polymer host includes polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0089] 18. The electrochemical cell of embodiment 10, wherein the polymer host is selected from the group consisting of: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), poly(acrylic acid) (PAA), polypropylene oxide (PPO), polyacrylonitrile (PAN), polymethacrylonitrile (PMAN), polymethyl methacrylate (PMMA), carboxymethyl cellulose (CMC), poly(vinyl alcohol) (PVA), polyvinyl pyrrolidone (PVP) and combinations thereof.
[0090] 19. The electrochemical cell of embodiment 10, wherein one or more of the following conditions are met:
[0091] (i) the combination of the lithium salt comprising sulfur and fluorine and the lithium salt comprising boron has a concentration of greater than or equal to about 1.2 M to less than or equal to about 4 M;
[0092] (ii) the lithium salt comprising sulfur and fluorine and the lithium salt comprising boron each have a concentration of greater than or equal to about 0.6 M to less than or equal to about 2 M;
[0093] (iii) a w / w ratio of the fluorinated plasticizer to the non-fluorinated plasticizer of from about 0.9:1 w / w to about 0.2:1 w / w; and
[0094] (iv) the polymer host is present in an amount of 0.5 wt % to about 40 wt %.
[0095] 20. The electrochemical cell of embodiment 10, wherein one or more of the following conditions are met:
[0096] (i) the lithium salt comprising sulfur and fluorine comprises lithium bis(trifluoromethanesulfonyl)imide (LiTFSI);
[0097] (ii) the boron-containing lithium salt comprises lithium tetrafluoroborate (LiBF4);
[0098] (iii) the fluorinated plasticizer comprises fluoroethylene carbonate (FEC);
[0099] (iv) the non-fluorinated plasticizer comprises gamma-butyrolactone (GBL); and
[0100] (v) The polymer host comprises polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0101] The above features and advantages and other features and advantages of the present disclosure are apparent from the following detailed description when taken in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0102] Additional features, advantages and details are set forth, by way of example only, in the following detailed description, which refers to the accompanying drawings, in which:
[0103] Figure 1 The possible evolution of the SEI layer on silicon produced by a polymer gel electrolyte containing ethylene carbonate (EC) and GBL is shown;
[0104] Figure 2A is a schematic diagram of an exemplary electrochemical battery cell;
[0105] Figure 2B is a schematic diagram of another exemplary electrochemical battery cell;
[0106] Figure 3 is a graph showing the capacity retention rates of the battery cells of Comparative Examples 1 and 2 and Examples 1 and 2;
[0107] Figure 4 is a graph showing the capacity retention rates of the battery cells of Comparative Examples 1 and 2 and Examples 1 and 2;
[0108] Figure 5 is a diagram showing low temperature startup of battery cells of Comparative Examples 1 and 2 and Examples 1 and 2;
[0109] Figure 6 is a scanning electron microscope (SEM) image of the silicon anode of Comparative Example 1 after testing for 100 cycles at 45° C.;
[0110] Figure 7 is a scanning electron microscope (SEM) image of the silicon anode of Comparative Example 2 after testing for 100 cycles at 45° C.;
[0111] Figure 8 is a scanning electron microscope (SEM) image of the silicon anode of Example 1 after testing at 45° C. for 100 cycles; and
[0112] Fig. 9 is a scanning electron microscope (SEM) image of the silicon anode of Example 2 after testing at 45°C for 100 cycles. DETAILED DESCRIPTION
[0113] The following description is merely exemplary in nature and is not intended to limit the present disclosure, its application, or uses. It should be understood that throughout the drawings, corresponding reference numerals indicate the same or corresponding parts and features.
[0114] According to an exemplary embodiment, a polymer gel electrolyte for a solid-state battery (SSB) and a method of forming and using the same are disclosed. A solid-state battery may include at least one solid component, such as at least one solid electrode, but in certain variations may also include a semi-solid or gel, liquid, or gas component. Such solid-state batteries may be incorporated into energy storage devices, such as rechargeable lithium-ion batteries, which can be used in automotive transportation applications (e.g., motorcycles, boats, tractors, buses, mobile homes, campers, and tanks). However, the present technology may also be used in other electrochemical devices, including, as non-limiting examples, aerospace components, consumer products, devices, buildings (e.g., houses, offices, sheds, and warehouses), office equipment and furniture, and industrial equipment machinery, agricultural or farm equipment, or heavy machinery. In various aspects, the present disclosure provides a rechargeable lithium-ion battery that exhibits high temperature resistance as well as improved safety and excellent power capacity and life performance.
[0115] I. Polymer Gel Electrolyte
[0116] Provided herein are polymer gel electrolytes for electrochemical cells such as semi-solid and solid-state batteries. The polymer gel electrolytes include lithium salts containing sulfur and fluorine, lithium salts containing boron, fluorinated plasticizers, non-fluorinated plasticizers, and polymer hosts. The w / w ratio of the fluorinated plasticizer to the non-fluorinated plasticizer is 9:1 to 1:9.
[0117] In any embodiment, the lithium salt comprising sulfur and fluorine may include a lithium cation (Li + ) and an anion selected from the group consisting of: bis-trifluoromethanesulfonimide (TFSI - ), bis(fluorosulfonyl)imide (FSI - ), trifluoromethanesulfonate - ), bis(pentafluoroethanesulfonyl)imide (BETI - ), cyclo-difluoromethane-1,1-bis(sulfonyl)imide (DMSI - ) and cyclo-hexafluoropropane-1,1-bis(sulfonyl)imide (HPSI - ); and the lithium salt containing boron may include a lithium cation (Li + ) and an anion selected from the group consisting of tetrafluoroborate (BF4 - ), bis(oxalato)borate (BOB - ), tetracyanoborate (bison - ), difluoro(oxalate)borate (DFOB - ) and bis(fluoromalonate)borate (BFMB -). For example, the lithium salt containing sulfur and fluorine may be lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and the lithium salt containing boron may be lithium tetrafluoroborate (LiBF4).
[0118] In any embodiment, the combination of a lithium salt comprising sulfur and fluorine and a lithium salt comprising boron can be present in a concentration of greater than or equal to about 0.6 M, greater than or equal to about 0.8 M, greater than or equal to about 1 M, greater than or equal to about 1.2 M, greater than or equal to about 1.4 M, greater than or equal to about 1.6 M, greater than or equal to about 1.8 M, greater than or equal to about 2 M, less than or equal to about 4 M, less than or equal to about 3.5 M, less than or equal to about 3 M, or less than or equal to about 2.5 M; or from greater than or equal to about 0.6 M to less than or equal to about 4 M, greater than or equal to about 0.8 M to less than or equal to about 4 M, greater than or equal to about 1 M to less than or equal to about 4 M, greater than or equal to about 1.2 M to less than or equal to about 4 M, or greater than or equal to about 1.6 M to less than or equal to about 3 M. Alternatively, the lithium salt containing sulfur and fluorine and the lithium salt containing boron may each independently be present at a concentration of greater than or equal to about 0.6 M, greater than or equal to about 0.8 M, greater than or equal to about 1 M, less than or equal to about 2 M, less than or equal to about 1.8 M, less than or equal to about 1.6 M, less than or equal to about 1.4 M, or less than or equal to about 1.2 M; or from greater than or equal to about 0.6 M to less than or equal to about 2 M, greater than or equal to about 0.8 M to less than or equal to about 1.8 M, or greater than or equal to about 1 M to less than or equal to about 1.6 M. The concentration of each of the lithium salt containing sulfur and fluorine and the lithium salt containing boron is based on the moles of the lithium salt containing sulfur and fluorine and the lithium salt containing boron / the total volume of the lithium salt containing sulfur and fluorine, the lithium salt containing boron, the fluorinated plasticizer, and the non-fluorinated plasticizer. Without wishing to be bound by any theory, it is believed that the combination of a lithium salt containing sulfur and fluorine and a lithium salt containing boron in the polymer gel electrolyte and / or the concentration of each of the lithium salt containing sulfur and fluorine and the lithium salt containing boron within the disclosed range can advantageously promote the desolvation process of lithium ions on the surface of the anode, for example, which can enhance high temperature cycling characteristics.
[0119] In any embodiment, the polymer gel electrolyte may include a fluorinated plasticizer and a non-fluorinated plasticizer. Examples of fluorinated plasticizers include, but are not limited to, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoropropylene carbonate (TFPC), methyl 2,2,2-trifluoroethyl carbonate, ethyl 2,2,2-trifluoroethyl carbonate, 2,2-difluoroethyl methyl carbonate, 2,2-difluoroethyl ethyl carbonate, 2,2-difluoroethyl acetate, 2,2,2-trifluoroethyl acetate, 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether, and other fluorine-based linear solvents and fluorine-based cyclic solvents. Examples of non-fluorinated plasticizers include, but are not limited to, gamma-butyrolactone (GBL), carbonate solvents (such as propylene carbonate (PC), glycerol carbonate, vinylene carbonate, and 1,2-butylene carbonate), lactones (such as delta-valerolactone), nitriles (such as succinonitrile, glutaronitrile, and adiponitrile), sulfones (such as tetramethylene sulfone, ethyl methyl sulfone, vinyl sulfone, phenyl sulfone, and benzyl sulfone), ethers (such as triethylene glycol dimethyl ether (triglyme, G3), tetraethylene glycol dimethyl ether (tetraglyme, G4), 1,3-dimethoxypropane, and 1,4-dioxane), and phosphates (such as triethyl phosphate and trimethyl phosphate). In any embodiment, the fluorinated plasticizer may be fluoroethylene carbonate (FEC), and the non-fluorinated plasticizer may be gamma-butyrolactone (GBL).
[0120] Without wishing to be bound by any theory, it is believed that due to the synergistic effect of fluorinated plasticizers (e.g., fluoroethylene carbonate (FEC)) and non-fluorinated plasticizers (e.g., γ-butyrolactone (GBL)), the polymer gel electrolyte is able to form a robust SEI on electroactive materials such as silicon with environmental friendliness, a desirable potential (about 0.3 volts (V)), and a high theoretical capacity (for Li 4.4 Si is 4200 milliamps per gram (mAh / g))), which has a high LiF content and appropriate elasticity to enhance battery cycling characteristics. For example, the following shows the possible electroreduction of FEC:
[0121]
[0122] And the possible electroreduction of GBL is shown as follows:
[0123]
[0124] The reduction of FEC in the polymer gel electrolyte can generate fluoride ions, which can lead to chemical attack of the silicon oxide surface passivation layer and the formation of a kinetically stable SEI mainly including LiF. The reduction of GBL in the polymer gel electrolyte can generate organic oligomer species, which can provide elasticity to maintain the integrity of the SEI to resist mechanical damage during volume expansion and contraction of the electroactive material (such as silicon). GBL with a high flash point and a wide liquid temperature range can provide abuse-tolerable and all-weather SSB. After cycling, the SEI on the anode can contain LiF in an amount of 10 to 50 wt%, such as 20 wt%, and organic oligomer species in an amount of 30 to 80 wt%.
[0125] Regarding the polymer gel electrolyte containing EC and GBL, the decomposition of EC / GBL in the polymer gel electrolyte can lead to the formation of, for example, oligomeric species, lithium ethylene dicarbonate salt (LEDC) and lithium carbonate (Li2CO3). Silicon dioxide or lithium silicate on silicon can further catalyze the thermal decomposition of LEDC to produce Li2CO3, Li2O, CO2, ethylene and lithium carboxylate, which are soluble in the polymer gel electrolyte or in a gaseous state, which may lead to an unstable and ineffective SEI. Figure 1 The possible evolution of the SEI layer on silicon resulting from a polymer gel electrolyte comprising EC and GBL is shown in FIG, and the possible decomposition reaction of EC is shown as follows:
[0126]
[0127] Figure 1 Delithiation and subsequent (re)lithiation are shown. Figure 1 In, Li x Si is denoted by reference numeral 100 , Si is denoted by reference numeral 200 , LiF is denoted by reference numeral 11 , PEO is denoted by reference numeral 12 , LEDC is denoted by reference numeral 13 , and Li 2 CO 3 is denoted by reference numeral 14 .
[0128] It has been found that the respective amounts of fluorinated plasticizer and non-fluorinated plasticizer, such as the weight ratio of fluorinated plasticizer to non-fluorinated plasticizer, can advantageously contribute to the battery having balanced low temperature discharge and high temperature cycle characteristics. For example, the weight (w / w) ratio of fluorinated plasticizer (e.g., fluoroethylene carbonate) to non-fluorinated plasticizer (e.g., γ-butyrolactone) can be about 3:7 w / w; or about 9:1 w / w to about 1:9 w / w, about 0.9:1 w / w to about 0.2:1 w / w, or about 0.8:1 w / w / to about 0.3:1 w / w.
[0129] Without wishing to be bound by any theory, it is believed that the surface area of the electroactive material can affect the w / w ratio of fluorinated plasticizer to non-fluorinated plasticizer in order to provide desirable performance for a battery containing the polymer gel electrolyte of the present disclosure. For example, the w / w ratio of fluorinated plasticizer to non-fluorinated plasticizer that provides desirable performance for a battery containing the polymer gel electrolyte of the present disclosure can be greater for electroactive materials with larger surface areas (e.g., nano-sized particles compared to micron-sized particles) than for electroactive materials with smaller surface areas.
[0130] Without wishing to be bound by any theory, it is believed that the combined amount of lithium salts containing sulfur and fluorine, lithium salts containing boron, fluorinated plasticizers, and non-fluorinated plasticizers can advantageously be able to improve battery performance in terms of rate performance, low temperature discharge, and high temperature cycle characteristics. In addition, the combination of lithium salts containing sulfur and fluorine (e.g., LiTFSI), lithium salts containing boron (e.g., LiB4), lithium salts containing boron, fluorinated plasticizers (FEC), and non-fluorinated plasticizers (GBL) can synergistically contribute to the formation of a robust passivation layer on the anode surface, which promotes the penetration of lithium cation solvates. In any embodiment, lithium salts containing sulfur and fluorine, lithium salts containing boron, fluorinated plasticizers, and non-fluorinated plasticizers can be present in an amount of greater than or equal to about 60 wt % to less than or equal to about 99.5 wt %, or about 95 wt %, based on the total weight of lithium salts containing sulfur and fluorine, lithium salts containing boron, fluorinated plasticizers, and non-fluorinated plasticizers, and the polymer host.
[0131] In any embodiment, the polymer host can be selected from: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), poly(acrylic acid) (PAA), polypropylene oxide (PPO), polyacrylonitrile (PAN), polymethacrylonitrile (PMAN), polymethyl methacrylate (PMMA), carboxymethyl cellulose (CMC), poly(vinyl alcohol) (PVA), polyvinyl pyrrolidone (PVP) and combinations thereof. In any embodiment, the polymer host can be polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP). The polymer host may be present in an amount of greater than or equal to about 0.5 wt %, greater than or equal to about 1 wt %, greater than or equal to about 2.5 wt %, greater than or equal to about 5 wt %, greater than or equal to about 10 wt %, greater than or equal to about 15 wt %, less than or equal to about 40 wt %, less than or equal to about 35 wt %, less than or equal to about 30 wt %, less than or equal to about 25 wt %, or less than or equal to about 20 wt %; or from greater than or equal to about 0.5 wt % to less than or equal to about 40 wt %, greater than or equal to about 1 wt % to less than or equal to about 30 wt %, greater than or equal to about 2.5 wt % to less than or equal to about 25 wt %, greater than or equal to about 5 wt % to less than or equal to about 20 wt %, based on the total weight of the polymer gel electrolyte composition.
[0132] In various aspects, the polymer gel electrolyte may include one or more combinations of the following: (i) a combination of a lithium salt comprising sulfur and fluorine and a lithium salt comprising boron having a concentration greater than or equal to about 1.2 M to less than or equal to about 4 M; (ii) the lithium salt comprising sulfur and fluorine and the lithium salt comprising boron each having a concentration greater than or equal to about 0.6 M to less than or equal to about 2 M; (iii) a w / w ratio of fluorinated plasticizer to non-fluorinated plasticizer of about 0.9:1 w / w to about 0.2:1 w / w; and (iv) the polymer host is present in an amount of 0.5 wt % to about 40 wt %, based on the total weight of the polymer gel electrolyte. Additionally or alternatively, the polymer gel electrolyte may include a combination of one or more of the following: (i) a lithium salt containing sulfur and fluorine including lithium bis(trifluoromethanesulfonyl)imide (LiTFSI); (ii) a lithium salt containing boron including lithium tetrafluoroborate (LiBF4); (iii) a fluorinated plasticizer including fluoroethylene carbonate (FEC); (iv) a non-fluorinated plasticizer including γ-butyrolactone (GBL); and (v) a polymer host including polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0133] Additionally or alternatively, the polymeric gel electrolyte may further include solid electrolyte particles dispersed or distributed therein. The solid electrolyte particles may have an average particle size greater than or equal to about 0.02 micrometers (μm) to less than or equal to about 20 μm, optionally greater than or equal to about 0.1 μm to less than or equal to about 10 μm, and in some aspects optionally greater than or equal to about 0.1 μm to less than or equal to about 1 μm.
[0134] In any embodiment, the solid electrolyte particles may comprise one or more oxide-based particles, sulfide-based particles, metal-doped or aliovalently substituted oxide particles, inactive oxide particles, nitride-based particles, hydride-based particles, halide-based particles, and borate-based particles.
[0135] In certain variations, the oxide-based particles may comprise one or more garnet ceramics, LISICON-type oxides, NASICON-type oxides, and perovskite-type ceramics. For example, the garnet ceramic may be selected from: Li7La3Zr2O 12 、Li 6.2 Ga 0.3 La 2.95 Rb 0.05 Zr2O 12 、Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 、Li 6.25 Al 0.25 La3Zr2O 12 、Li 6.75 La3Zr 1.75 Nb 0.25 O 12 and combinations thereof. The LISICON-type oxide may be selected from: Li 2+2x Zn 1-x GeO4 (where 0 < x < 1), Li 14 Zn(GeO4)4, Li 3+x (P 1-x Si x )O4 (where 0 < x < 1), Li 3+x Ge x V 1-x O4 (where 0 < x < 1) and combinations thereof. The NASICON-type oxide may be defined by LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr, and La. For example, in certain variations, the NASICON-type oxide may be selected from: Li 1+x Al xGe 2-x (PO4)3(LAGP) (where 0 ≤ x ≤ 2), Li 1.4 Al 0.4 Ti 1.6 (PO4)3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3, and combinations thereof. The perovskite-type ceramic can be selected from: Li 3.3 La 0.53 TiO3, LiSr 1.65 Zr 1.3 Ta 1.7 O9, Li 2x- y Sr 1-x Ta y Zr 1-y O3 (where x = 0.75y and 0.60 < y < 0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O3, Li 3x La (2 / 3-x) TiO3 (where 0 < x < 0.25) and combinations thereof.
[0136] In certain variants, the metal-doped or aliovalent-substituted oxide particles can include (e.g., only include) aluminum (Al)- or niobium (Nb)-doped Li7La3Zr2O 12 、antimony (Sb)-doped Li7La3Zr2O 12 、gallium (Ga)-doped Li7La3Zr2O 12 、chromium (Cr) and / or vanadium (V)-substituted LiSn2P3O 12 、aluminum (Al)-substituted Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (where 0 < x < 2 and 0 < y < 3) and combinations thereof.
[0137] In certain variants, the sulfide-based particles can include (e.g., only include) pseudo-binary sulfides, pseudo-tertiary sulfides, and / or pseudo-quaternary sulfides. Exemplary pseudo-binary sulfide systems include the Li2S-P2S5 system (such as Li3PS4, Li7P3S 11 and Li 9.6 P3S 12), Li2S–SnS2 system (such as Li4SnS4), Li2S–SiS2 system, Li2S–GeS2 system, Li2S–B2S3 system, Li2S–Ga2S3 system, Li2S–P2S3 system, Li2S–Al2S3 system, Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.3 , lithium argyrodite Li6PS5X (wherein X is one of Cl, Br and I). Exemplary pseudo-ternary sulfide systems include Li2O-Li2S-P2S5 system, Li2S-P2S5-P2O5 system, Li2S-P2S5-GeS2 system (such as Li 3.25 Ge 0.25 P 0.75 S4 (sulfo-LISICON) and Li 10 GeP2S 12 (LGPS)), Li2S–P2S5–LiX system (where X is one of F, Cl, Br and I) (such as Li6PS5Br, Li6PS5Cl, L7P2S8I and Li4PS4I), Li2S–As2S5–SnS2 system (such as Li 3.833 Sn 0.833 As 0.166 S4), Li2S–P2S5–Al2S3 system, Li2S–LiX–SiS2 system (where X is one of F, Cl, Br and I), 0.4LiI·0.6Li4SnS4 and Li 11 Si2PS 12 Exemplary pseudo-quaternary sulfide systems include the Li2O–Li2S–P2S5–P2O5 system, Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0..3 , Li 9.6 P3S 12 、Li7P3S 11 、Li9P3S9O3、Li 10.35 Ge 1.35 P 1.65 S 12 , Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.1.9 S 12 , Li 10 (Si0.5 Ge 0.5 )P2S 12 , Li 10 (Ge 0.5 Sne 0.5 )P2S 12 , Li 10 (Si 0.5 Sn 0.5 )P2S 12 、Li7P 2.9 Mn 0.1 S 10.7 I 0.3 , Li 3.833 Sn 0.833 As 0.166 S4, LiI-Li4SnS4, Li4SnS4 and Li 10.35 [Sn 0.27 Si 1.08 ]P 1.65 S 12 .
[0138] In certain embodiments, the inactive oxide particles may include (e.g., only include) SiO2, Al2O3, TiO2, ZrO2, and combinations thereof; the nitride-based particles may include (e.g., only include) Li3N, Li7PN4, LiSi2N3, and combinations thereof; the hydride-based particles may include (e.g., only include) LiBH4, LiBH4-LiX (wherein x=Cl, Br or I), LiNH2, Li2NH, LiBH4-LiNH2, Li3AlH6, and combinations thereof; the halide-based particles may include (e.g., only include) LiI, Li3InCl6, Li2CdCl4, Li2MgCl4, LiCdI4, Li2ZnI4, Li3OCl, Li3YCl6, Li3YBr6, and combinations thereof; and the borate-based particles may include (e.g., only include) Li2B4O7, Li2O-B2O3-P2O5, and combinations thereof.
[0139] Although not shown, those skilled in the art will recognize that in some cases, one or more binder particles (also referred to herein as polymer binders) can be mixed with solid electrolyte particles. The one or more polymer binders may include (e.g., only include) polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene propylene diene rubber (EPDM), nitrile rubber (NBR), styrene-butadiene rubber (SBR) and lithium polyacrylate (LiPAA).
[0140] The polymer gel electrolyte can be prepared by mixing a lithium salt containing sulfur and fluorine, a lithium salt containing boron, a fluorinated plasticizer, a non-fluorinated plasticizer and a polymer host with a suitable solvent to form a gel precursor solution. Suitable solvents include, but are not limited to, various alkyl carbonates, such as linear carbonates (e.g., dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC)), aliphatic carboxylates (e.g., methyl formate, methyl acetate, methyl propionate), chain structure ethers (e.g., 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane) and cyclic ethers (e.g., tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane). The gel precursor solution can also optionally include solid electrolyte particles as described. The gel precursor solution can be applied to one or more of the anode, cathode and porous separator / membrane and penetrate the pores of the anode, cathode and / or porous separator / membrane. After application, the gel precursor solution may be volatilized by any suitable method, such as drying at a suitable temperature (eg, ~25°C) for a suitable amount of time (eg, ~1 hour) to remove the solvent and form a polymer gel electrolyte.
[0141] II. Electrochemical Cells
[0142] Provided herein are electrochemical cells, such as semi-solid or solid-state batteries, comprising the polymer gel electrolytes described herein. Figure 2A and 2B An exemplary and schematic illustration of a solid-state electrochemical cell (also referred to as a "solid-state battery" and / or "battery") 20 for circulating lithium ions is shown in FIG. The battery 20 includes a negative electrode 22 (also referred to as a negative electrode layer 22), a positive electrode 24 (also referred to as a positive electrode layer 24), and an electrolyte layer 26 disposed between the two electrodes 22, 24. The electrolyte layer 26 can be a solid or semi-solid separator layer containing a polymer gel electrolyte 30 described herein, which is, for example, distributed on and within a porous separator 38 that physically separates the negative electrode 22 from the positive electrode 24. Thus, the space between the negative electrode 22 and the positive electrode 24 can be filled with the polymer gel electrolyte 30. If there are pores inside the negative electrode 22 and the positive electrode 24, the pores can also be filled with the polymer gel electrolyte 30. The polymer gel electrolyte 30 can impregnate, penetrate or wet the surfaces of the negative electrode 22, the positive electrode 24, and the porous separator 38 and fill the pores of the negative electrode 22, the positive electrode 24, and the porous separator 38. Additionally or alternatively, such as Figure 2BAs shown in , the electrolyte layer 26 may include a plurality of solid electrolyte particles 36 as described herein. The negative electrode current collector 32 may be located at or near the negative electrode 22, and the positive electrode current collector 34 may be located at or near the positive electrode 24. The negative electrode current collector 32 and the positive electrode current collector 34 collect free electrons from the external circuit 40 and move the free electrons to the external circuit 40, respectively. The external circuit 40 and the load device 42 may be interrupted to connect the negative electrode 22 (through its current collector 32) and the positive electrode 24 (through its current collector 34). The negative electrode 22, the positive electrode 24 and the separator 38 may each further include a polymer gel electrolyte 30 capable of conducting lithium ions. The separator 38 acts as an electrical insulator and mechanical support by being sandwiched between the negative electrode 22 and the positive electrode 24 to prevent physical contact and thereby prevent a short circuit from occurring. In addition to providing a physical barrier between the two electrodes 22, 24, the separator 38 can also provide a path of least resistance for the internal passage of lithium ions (and related anions) to facilitate the function of the battery 20. The separator 38 also contains the polymer gel electrolyte 30 in a network of open voids to facilitate the function of the battery 20 during lithium ion cycling.
[0143] The battery 20 can generate current during discharge by a reversible electrochemical reaction that occurs when the external circuit 40 is closed (to connect the negative electrode 22 and the positive electrode 24) and when the negative electrode 22 contains a relatively larger amount of intercalated lithium. The chemical potential difference between the positive electrode 24 and the negative electrode 22 drives electrons generated at the negative electrode 22 by a reaction such as oxidation of the intercalated lithium toward the positive electrode 24 through the external circuit 40. Lithium ions, also generated at the negative electrode, are simultaneously transferred toward the positive electrode 24 through the electrolyte layer 26. The electrons flow through the external circuit 40, and the lithium ions migrate across the electrolyte layer 26 to form intercalated lithium at the positive electrode 24. The current through the external circuit 40 can be utilized and directed through the load device 42 until the intercalated lithium in the negative electrode 22 is depleted and the capacity of the lithium ion battery 20 is reduced.
[0144] The lithium-ion battery 20 can be charged or re-powered / re-energized at any time by connecting an external power source to the lithium-ion battery 20 to reverse the electrochemical reactions that occur during the battery discharge process. Connecting the external power source to the lithium-ion battery 20 promotes the non-spontaneous oxidation of intercalated lithium at the positive electrode 24 to produce electrons and lithium ions. The electrons (which flow back to the negative electrode 22 through the external circuit 40) and the lithium ions (which are carried back to the negative electrode 22 by the electrolyte layer 26) are recombined at the negative electrode 22 and replenished with intercalated lithium for consumption during the next battery discharge event. Thus, a complete discharge event and a subsequent complete charge event are considered to be a cycle, in which lithium ions circulate between the positive electrode 24 and the negative electrode 22. The external power source that can be used to charge the lithium-ion battery 20 can vary depending on the size, construction, and specific end use of the lithium-ion battery 20. Some notable and exemplary external power sources include, but are not limited to, AC wall outlets and automotive alternators. In many configurations, each of the negative electrode current collector 32, the negative electrode 22, the electrolyte layer 26, the positive electrode 24, and the positive electrode current collector 34 is prepared as a relatively thin layer (e.g., a few microns to a millimeter or less in thickness) and assembled in a layer form connected in a series arrangement to provide suitable power, battery voltage, and power packaging, such as obtaining a series-connected unit cell core ("SECC"). In various other cases, the battery 20 may further include electrodes 22, 24 connected in parallel to provide suitable power, battery voltage, and power, such as obtaining a parallel-connected unit cell core ("PECC").
[0145] In addition, the battery 20 may include a variety of other components that are not depicted herein but are known to those skilled in the art. For example, as a non-limiting example, the lithium-ion battery 20 may include a housing, gaskets, end caps, tabs, battery terminals, and any other conventional components or materials that may be located within the battery 20 (including between or around the negative electrode 22, the positive electrode 24, and / or the electrolyte layer 26).
[0146] As described above, the size and shape of the lithium-ion battery pack 20 can vary depending on the specific application for which it is designed. Battery-powered vehicles and handheld consumer electronic devices are two examples in which the battery pack 20 is most likely to be designed to different size, capacity, and power output specifications. The battery pack 20 can also be connected in series or parallel with other similar lithium-ion cells or batteries to produce a greater voltage output and power density (if required by the load device 42).
[0147] Thus, the battery pack 20 can generate an electric current to a load device 42, which can be operably connected to the external circuit 40. The load device 42 can be powered in whole or in part by the current through the external circuit 40 when the lithium-ion battery pack 20 is discharged. Although the load device 42 can be any number of known electric devices, as non-limiting examples, some specific examples of power-consuming load devices include electric motors for hybrid electric vehicles or all-electric vehicles, laptop computers, tablet computers, cellular phones, and cordless power tools or appliances. The load device 42 can also be a power generation device that charges the battery pack 20 for the purpose of storing electrical energy.
[0148] The present technology relates to improved electrochemical cells, particularly lithium ion batteries. In various cases, such batteries are used in vehicle or automotive transportation applications (e.g., motorcycles, boats, tractors, buses, motorbikes, trailers, campers, and tanks). However, the present technology can also be used in many other industries and applications, including, as non-limiting examples, aerospace components, consumer products, devices, buildings (e.g., houses, offices, sheds, and warehouses), office equipment and furniture, and industrial equipment machinery, agricultural or farm equipment, or heavy machinery.
[0149] A. Positive electrode
[0150] The positive electrode 24 can be formed of a first electroactive material in which lithium insertion and extraction can occur sufficiently while serving as a positive electrode terminal of the battery 20. It is contemplated herein that the first electroactive material can be in particle form and can have a circular geometry or an axial geometry. The term "axial geometry" refers to particles that generally have a rod, fiber, or other cylindrical shape, which has a distinct long axis or slender axis. Typically, the aspect ratio (AR) of a cylinder (such as a fiber or rod) is defined as AR=L / D, where L is the length of the longest axis and D is the diameter of the cylinder or fiber. Exemplary axial geometry electroactive material particles suitable for the present disclosure can have a high aspect ratio, for example, from about 10 to about 5,000. In certain variations, the first electroactive material particles having an axial geometry include fibers, wires, flakes, whiskers, filaments, tubes, rods, and the like. The term "circular geometry" is generally applicable to particles having a lower aspect ratio, such as an aspect ratio closer to 1 (e.g., less than 10). It should be noted that the particle geometry can vary from a true circle and can include, for example, oblong or ellipsoidal shapes, including elongated or oblate spheres, agglomerated particles, polygonal (e.g., hexagonal) particles, or other shapes generally having a low aspect ratio. An oblate spheroid can have a relatively high aspect ratio disc shape. Thus, particles of generally circular geometry are not limited to relatively low aspect ratio and spherical shapes.
[0151] The positive electrode 24 can be in the form of a layer having a thickness greater than or equal to about 1 μm to less than or equal to about 1,000 μm, optionally greater than or equal to about 5 μm to less than or equal to about 400 μm, and in some aspects optionally greater than or equal to about 10 μm to less than or equal to about 300 μm. In some variations, the positive electrode 24 can be defined by a plurality of positive electrode electroactive particles 35, such as comprising a first electroactive material. The positive electrode electroactive particles 35 can have an average particle size greater than or equal to about 0.01 μm to less than or equal to about 50 μm, and in some aspects optionally greater than or equal to about 1 μm to less than or equal to about 20 μm. The positive electrode 24 can also include a polymeric binder material to structurally reinforce the lithium-based active material and the conductive material.
[0152] An exemplary common type of known material that can be used to form the positive electrode 24 is a layered lithium transition metal oxide. For example, in some embodiments, the positive electrode layer 24 can comprise Li (1+x) Mn2O4, where 0.1 ≤ x ≤ 1; LiMn (2-x) Ni x O4, where 0 ≤ x ≤ 0.5; LiCoO2; Li(Ni x Mn y Co z )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1 and x + y + z = 1; LiNi (1-x-y) Co x M y O2, where 0 < x < 0.2, y < 0.2 and M is Al, Mg or Ti; LiFePO4, LiMn 2-x Fe x PO4, where 0 < x < 0.3; LiNiCoAlO2; LiMPO4, where M is at least one of Fe, Ni, Co and Mn; Li(Ni x Mn y Co z Al p )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ P ≤ 1, x + y + z + p = 1 (NCMA); LiNiMnCoO2; Li2Fe x M 1-x PO4 (M = Mn and / or Ni, 0 ≤ x ≤ 1); LiMn2O4 (LMO); LiFeSiO4; LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622), LiMnO2, LiNi 0.5 Mn 1.5O4, LiV2(PO4)3, activated carbon, sulfur (e.g., greater than 60 wt % based on the total weight of the positive electrode) or a combination thereof. In certain aspects, the positive electrode electroactive particles 35 can be coated (e.g., with LiNbO3 and / or Al2O3) and / or the positive electrode electroactive material can be doped (e.g., with aluminum and / or magnesium).
[0153] Although not shown, in some variations, the positive electrode 24 may optionally include a conductive material and / or a polymer binder as described herein. For example, the positive electroactive particles 35 may optionally be mixed with one or more conductive materials (not shown) that provide an electronic conduction path and / or at least one polymer binder material (not shown) that improves the structural integrity of the positive electrode 24.
[0154] Examples of conductive materials include, but are not limited to, carbon black (such as Super P), graphite, acetylene black (such as KETCHEN TM Black or DENKA TM Black), carbon nanotubes, carbon fibers, carbon nanofibers, graphene, graphene nanosheets, graphene oxide, nitrogen-doped carbon, metal powders (e.g., copper, nickel, steel, or iron), liquid metals (e.g., Ga, GaInSn), conductive polymers (e.g., including polyaniline, polythiophene, polyacetylene, polypyrrole, etc.), and combinations thereof. The term "graphene nanosheet" as used herein refers to a nanoplate or stack of graphene layers. Such conductive materials in particle form may have a circular geometry or an axial geometry as described above.
[0155] Examples of suitable polymer binders include, but are not limited to, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), ethylene propylene diene rubber (EPDM), carboxymethyl cellulose (CMC), nitrile rubber (NBR), styrene-butadiene rubber (SBR), styrene-ethylene-butylene-styrene copolymer (SEBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), poly (acrylic acid) (PAA), polyimide, polyamide, sodium alginate, lithium alginate and combinations thereof. In some embodiments, the polymer binder can be a non-aqueous solvent-based polymer or an aqueous-based polymer. The first electroactive material can be mixed with a conductive material and / or at least one polymer binder. For example, the first electroactive material and the optional conductive material can be slurry-casted with such a binder and applied to a current collector.
[0156] In any embodiment, the first electroactive material can be present in the positive electrode 24 in an amount of greater than or equal to about 50 wt %, greater than or equal to about 60 wt %, greater than or equal to about 70 wt %, greater than or equal to about 80 wt %, greater than or equal to about 90 wt %, greater than or equal to about 95 wt %, or about 99 wt %; or about 50 wt % to about 99 wt %, about 70 wt % to about 99 wt %, or about 90 wt % to about 99 wt %, based on the total weight of the positive electrode.
[0157] Additionally or alternatively, the conductive material and the polymer binder can each independently be present in the positive electrode in an amount of about 0.5 wt % to about 20 wt %, about 1 wt % to about 15 wt %, or about 1 wt % to about 10 wt %, based on the total weight of the positive electrode.
[0158] Although not shown, in certain variations, the positive electrode 24 may optionally include solid electrolyte particles as described herein. The solid electrolyte particles may include one or more oxide-based particles, sulfide-based particles, metal-doped or alivalently substituted oxide particles, inactive oxide particles, nitride-based particles, hydride-based particles, halide-based particles, and borate-based particles.
[0159] In certain variations, the oxide-based particles may include one or more garnet ceramics, LISICON-type oxides, NASICON-type oxides, and perovskite-type ceramics. For example, the garnet ceramic may be selected from: Li7La3Zr2O 12 , Li 6.2 Ga 0.3 La 2.95 R 0.05 Zr2O 12 , Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 , Li 6.25 Al 0.25 La3Zr2O 12 , Li 6.75 Ln3Z 1.75 Nb 0.25 O 12 And combinations thereof. The LISICON type oxide may be selected from: Li 2+2x Zn 1-x GeO4 (where 0 <x<1)、Li 14 Zn(GeO4)4、Li 3+x (P 1-x Si x)O4 (where 0 < x < 1), Li 3+x Ge x V 1-x O4 (where 0 < x < 1) and combinations thereof. The NASICON-type oxide can be defined by LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr, and La. For example, in certain variations, the NASICON-type oxide can be selected from: Li 1+x Al x Ge 2-x (PO4)3 (LAGP) (where 0 ≤ x ≤ 2), Li 1.4 Al 0.4 Ti 1.6 (PO4)3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3, and combinations thereof. The perovskite-type ceramic can be selected from: Li 3.3 La 0.53 TiO3, LiSr 1.65 Zr 1.3 Ta 1.7 O9, Li 2x- y Sr 1-x Ta y Zr 1-y O3 (where x = 0.75y and 0.60 < y < 0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O3, Li 3x La (2 / 3-x) TiO3 (where 0 < x < 0.25) and combinations thereof.
[0160] In certain variations, the metal-doped or aliovalent-substituted oxide particles can include (e.g., only include) aluminum (Al)-doped Li7La3Zr2O 12 、antimony (Sb)-doped Li7La3Zr2O 12 、gallium (Ga)-doped Li7La3Zr2O 12 、chromium (Cr) and / or vanadium (V)-substituted LiSn2P3O 12 、aluminum (Al)-substituted Li 1+x+y Al x Ti 2-x Si y P 3-y O 12(where 0 < x < 2 and 0 < y < 3) and combinations thereof.
[0161] In some variations, the sulfide-based particles can include (e.g., consist essentially of) pseudo-binary sulfides, pseudo-tertiary sulfides, and / or pseudo-quaternary sulfides. Exemplary pseudo-binary sulfide systems include the Li2S-P2S5 system (such as Li3PS4, Li7P3S 11 and Li 9.6 P3S 12 ), the Li2S–SnS2 system (such as Li4SnS4), the Li2S–SiS2 system, the Li2S–GeS2 system, the Li2S–B2S3 system, the Li2S–Ga2S3 system, the Li2S–P2S3 system, the Li2S–Al2S3 system, Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.3 , the lithium thiogermanate Li6PS5X (where X is one of Cl, Br, and I). Exemplary pseudo-tertiary sulfide systems include the Li2O–Li2S–P2S5 system, the Li2S–P2S5–P2O5 system, the Li2S–P2S5–GeS2 system (such as Li 3.25 Ge 0.25 P 0.75 S4 (thio-LISICON) and Li 10 GeP2S 12 (LGPS)), the Li2S–P2S5–LiX system (where X is one of F, Cl, Br, and I) (such as Li6PS5Br, Li6PS5Cl, L7P2S8I, and Li4PS4I), the Li2S–As2S5–SnS2 system (such as Li 3.833 Sn 0.833 As 0.166 S4), the Li2S–P2S5–Al2S3 system, the Li2S–LiX–SiS2 system (where X is one of F, Cl, Br, and I), 0.4LiI·0.6Li4SnS4, and Li 11 Si2PS 12 . Exemplary pseudo-quaternary sulfide systems include the Li2O–Li2S–P2S5–P2O5 system, Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0..3 , Li 9.6 P3S 12 , Li7P3S 11 , Li9P3S9O3, Li 10.35 Ge1.35 P 1.65 S 12 , Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.1.9 S 12 , Li 10 (Si 0.5 Ge 0.5 )P2S 12 , Li 10 (Ge 0.5 Sne 0.5 )P2S 12 , Li 10 (Si 0.5 Sn 0.5 )P2S 12 、Li7P 2.9 Mn 0.1 S 10.7 I 0.3 , Li 3.833 Sn 0.833 As 0.166 S4, LiI-Li4SnS4, Li4SnS4 and Li 10.35 [Sn 0.27 Si 1.08 ]P 1.65 S 12 .
[0162] In certain embodiments, the inactive oxide particles may include (e.g., only include) SiO2, Al2O3, TiO2, ZrO2, and combinations thereof; the nitride-based particles may include (e.g., only include) Li3N, Li7PN4, LiSi2N3, and combinations thereof; the hydride-based particles may include (e.g., only include) LiBH4, LiBH4-LiX (wherein x=Cl, Br or I), LiNH2, Li2NH, LiBH4-LiNH2, Li3AlH6, and combinations thereof; the halide-based particles may include (e.g., only include) LiI, Li3InCl6, Li2CdCl4, Li2MgCl4, LiCdI4, Li2ZnI4, Li3OCl, Li3YCl6, Li3YBr6, and combinations thereof; and the borate-based particles may include (e.g., only include) Li2B4O7, Li2O-B2O3-P2O5, and combinations thereof.
[0163] Additionally or alternatively, based on the total weight of the positive electrode, the solid electrolyte particles may be independently present in the positive electrode in an amount of about 0.5 wt % to about 20 wt %, about 1 wt % to about 15 wt %, or about 1 wt % to about 10 wt %. In some variations, the positive electrode may include 30 wt % to 98 wt % of the first electroactive material, 0 wt % to 50 wt % of the solid electrolyte particles, 0 wt % to 30 wt % of the conductive material, 0 wt % to 20 wt % of the polymer binder, and 0 wt % to 30 wt % of the polymer gel electrolyte.
[0164] B. Negative electrode
[0165] The negative electrode 22 includes a second electroactive material as a lithium matrix material capable of serving as a negative electrode terminal of a lithium-ion battery. The negative electrode 22 may be in the form of a layer having a thickness of greater than or equal to about 1 μm to less than or equal to about 1,000 μm, optionally greater than or equal to about 5 μm to less than or equal to about 400 μm, and in some aspects optionally greater than or equal to about 10 μm to less than or equal to about 300 μm. In some variations, the negative electrode 22 may be defined by a plurality of negative electroactive particles 33, for example, comprising a second electroactive material. The negative electroactive particles 33 may have an average particle size of greater than or equal to about 0.01 μm to less than or equal to about 50 μm, and in some aspects optionally greater than or equal to about 1 μm to less than or equal to about 20 μm.
[0166] The second electroactive material may be formed of or include one or more carbonaceous negative electrode electroactive materials, such as graphite, mesocarbon microbeads (MCMB), graphite carbon fibers, expanded graphite, soft carbon, hard carbon, natural graphite, graphene, or carbon nanotubes (CNTs). Additionally or alternatively, the second electroactive material may include a lithium alloy, such as, but not limited to, a lithium silicon alloy, a lithium aluminum alloy, a lithium indium alloy, a lithium tin alloy, or a combination thereof. The negative electrode 22 may optionally further include silicon, tin oxide, aluminum, indium, zinc, germanium, silicon oxide, titanium oxide, lithium titanate, iron sulfide (FeS), Li4Ti5O 12 and one or more of a combination thereof, such as silicon mixed with graphite. Non-limiting examples of silicon-containing electroactive materials include silicon (amorphous or crystalline) or binary and ternary alloys containing silicon, such as Si-Sn, SiSnFe, SiSnAl, SiFeCo, and the like. In any embodiment, the second electroactive material can be silicon. In other variations, the negative electrode 22 can be a metal film or foil, such as a lithium metal film or a lithium-containing foil. The second electroactive material can be in particle form and can have a circular geometry or an axial geometry as described herein.
[0167] Although not shown, in some variations, the negative electrode 22 may optionally include a conductive material and / or a polymer binder as described herein. For example, the negative electroactive particles 33 may optionally be mixed with one or more conductive materials (not shown) that provide an electronic conduction path and / or at least one polymer binder material (not shown) that improves the structural integrity of the negative electrode 22.
[0168] Examples of conductive materials include, but are not limited to, carbon black (such as Super P), acetylene black (such as KETCHEN TM Black or DENKA TM Black), carbon nanotubes, carbon fibers, carbon nanofibers, graphene, graphene nanosheets, graphene oxide, nitrogen-doped carbon, metal powders (e.g., copper, nickel, steel, or iron), liquid metals (e.g., Ga, GaInSn), conductive polymers (e.g., including polyaniline, polythiophene, polyacetylene, polypyrrole, etc.), and combinations thereof. Such conductive materials in particle form may have a circular geometry or an axial geometry as described above.
[0169] Examples of suitable polymer binders include, but are not limited to, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), ethylene propylene diene rubber (EPDM), carboxymethyl cellulose (CMC), nitrile rubber (NBR), styrene-butadiene rubber (SBR), styrene-ethylene-butylene-styrene copolymer (SEBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), poly (acrylic acid) (PAA), polyimide, polyamide, sodium alginate, lithium alginate, and combinations thereof. In some embodiments, the polymer binder may be a non-aqueous solvent-based polymer or a water-based polymer. In particular, the polymer binder may be a non-aqueous solvent-based polymer that exhibits less capacity decay, provides a more robust mechanical network and improved mechanical properties to more effectively handle silicon particle expansion, and has good chemical resistance and heat resistance. For example, the polymer binder may include polyimide, polyamide, polyacrylonitrile, polyacrylic acid, salts of polyacrylic acid (e.g., potassium, sodium, lithium), polyacrylamide, polyvinyl alcohol, carboxymethyl cellulose, or a combination thereof. The first electroactive material may be mixed with a conductive material and / or at least one polymer binder. For example, the first electroactive material and optional conductive material may be slurry cast together with such a binder and applied to a current collector.
[0170] In various aspects, based on the total weight of the negative electrode, the second electroactive material may be present in the negative electrode 22 in an amount of about 70 wt % to about 100 wt %, about 70 wt % to about 98 wt %, about 70 wt % to about 95 wt %, about 80 wt % to about 95 wt %. Additionally or alternatively, based on the total weight of the negative electrode, the conductive material and the polymer binder may each independently be present in the negative electrode in an amount of about 0.5 wt % to about 30 wt %, about 1 wt % to about 25 wt %, about 1 wt % to about 20 wt %, about 1 wt % to about 10 wt %, about 3 wt % to about 20 wt %, or about 5 wt % to about 15 wt %. In certain variations, the negative electrode may include 30 wt % to 98 wt % of the second electroactive material, 0 wt % to 50 wt % of the solid electrolyte particles, 0 wt % to 30 wt % of the conductive material, 0 wt % to 20 wt % of the polymer binder, and 0 wt % to 30 wt % of the polymer gel electrolyte.
[0171] Although not shown, in certain variations, the negative electrode 22 may optionally include solid electrolyte particles as described herein. The solid electrolyte particles may include one or more oxide-based particles, sulfide-based particles, metal-doped or alivalently substituted oxide particles, inactive oxide particles, nitride-based particles, hydride-based particles, halide-based particles, and borate-based particles.
[0172] In certain variations, the oxide-based particles may include one or more garnet ceramics, LISICON-type oxides, NASICON-type oxides, and perovskite-type ceramics. For example, the garnet ceramic may be selected from: Li7La3Zr2O 12 , Li 6.2 Ga 0.3 La 2.95 R 0.05 Zr2O 12 , Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 , Li 6.25 Al 0.25 La3Zr2O 12 , Li 6.75 Ln3Z 1.75 Nb 0.25 O 12 And combinations thereof. The LISICON type oxide may be selected from: Li 2+2x Zn 1-x GeO4 (where 0 <x<1)、Li 14 Zn(GeO4)4、Li3+x (P 1-x Si x )O4 (where 0 < x < 1), Li 3+x Ge x V 1-x O4 (where 0 < x < 1) and combinations thereof. The NASICON-type oxide can be defined by LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr, and La. For example, in certain variants, the NASICON-type oxide can be selected from: Li 1+x Al x Ge 2-x (PO4)3 (LAGP) (where 0 ≤ x ≤ 2), Li 1.4 Al 0.4 Ti 1.6 (PO4)3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3, and combinations thereof. The perovskite-type ceramic can be selected from: Li 3.3 La 0.53 TiO3, LiSr 1.65 Zr 1.3 Ta 1.7 O9, Li 2x- y Sr 1-x Ta y Zr 1-y O3 (where x = 0.75y and 0.60 < y < 0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4 Zr 1 / 4 O3, Li 3x La (2 / 3-x) TiO3 (where 0 < x < 0.25) and combinations thereof.
[0173] In certain variants, the metal-doped or heterovalently substituted oxide particles can include (e.g., consist of) aluminum (Al)- or niobium (Nb)-doped Li7La3Zr2O 12 antimony (Sb)-doped Li7La3Zr2O 12 gallium (Ga)-doped Li7La3Zr2O 12 chromium (Cr) and / or vanadium (V)-substituted LiSn2P3O 12 aluminum (Al)-substituted Li 1+x+y Al x Ti 2-x Si yP 3-y O 12 (where 0 < x < 2 and 0 < y < 3) and combinations thereof.
[0174] In some variations, the sulfide-based particles can include (e.g., consist of only) pseudo-binary sulfides, pseudo-ternary sulfides, and / or pseudo-quaternary sulfides. Exemplary pseudo-binary sulfide systems include the Li2S-P2S5 system (such as Li3PS4, Li7P3S 11 and Li 9.6 P3S 12 ), the Li2S–SnS2 system (such as Li4SnS4), the Li2S–SiS2 system, the Li2S–GeS2 system, the Li2S–B2S3 system, the Li2S–Ga2S3 system, the Li2S–P2S3 system, the Li2S–Al2S3 system, Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.3 , the lithium thiogermanate Li6PS5X (where X is one of Cl, Br, and I). Exemplary pseudo-ternary sulfide systems include the Li2O–Li2S–P2S5 system, the Li2S–P2S5–P2O5 system, the Li2S–P2S5–GeS2 system (such as Li 3.25 Ge 0.25 P 0.75 S4 (thiophosphate LISICON) and Li 10 GeP2S 12 (LGPS)), the Li2S–P2S5–LiX system (where X is one of F, Cl, Br, and I) (such as Li6PS5Br, Li6PS5Cl, L7P2S8I, and Li4PS4I), the Li2S–As2S5–SnS2 system (such as Li 3.833 Sn 0.833 As 0.166 S4), the Li2S–P2S5–Al2S3 system, the Li2S–LiX–SiS2 system (where X is one of F, Cl, Br, and I), 0.4LiI·0.6Li4SnS4, and Li 11 Si2PS 12 . Exemplary pseudo-quaternary sulfide systems include the Li2O–Li2S–P2S5–P2O5 system, Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0..3 , Li 9.6 P3S 12 Li7P3S 11、Li9P3S9O3、Li 10.35 Ge 1.35 P 1.65 S 12 , Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.1.9 S 12 , Li 10 (Si 0.5 Ge 0.5 )P2S 12 , Li 10 (Ge 0.5 Sne 0.5 )P2S 12 , Li 10 (Si 0.5 Sn 0.5 )P2S 12 、Li7P 2.9 Mn 0.1 S 10.7 I 0.3 , Li 3.833 Sn 0.833 As 0.166 S4, LiI-Li4SnS4, Li4SnS4 and Li 10.35 [Sn 0.27 Si 1.08 ]P 1.65 S 12 .
[0175] In certain embodiments, the inactive oxide particles may include (e.g., only include) SiO2, Al2O3, TiO2, ZrO2, and combinations thereof; the nitride-based particles may include (e.g., only include) Li3N, Li7PN4, LiSi2N3, and combinations thereof; the hydride-based particles may include (e.g., only include) LiBH4, LiBH4-LiX (wherein x=Cl, Br or I), LiNH2, Li2NH, LiBH4-LiNH2, Li3AlH6, and combinations thereof; the halide-based particles may include (e.g., only include) LiI, Li3InCl6, Li2CdCl4, Li2MgCl4, LiCdI4, Li2ZnI4, Li3OCl, Li3YCl6, Li3YBr6, and combinations thereof; and the borate-based particles may include (e.g., only include) Li2B4O7, Li2O-B2O3-P2O5, and combinations thereof.
[0176] C. Current Collector
[0177] The positive electrode current collector 34 and / or the negative electrode current collector 32 may include at least one of stainless steel, aluminum, nickel, iron, titanium, copper, tin, or any other conductive material known to those skilled in the art. Additionally or alternatively, the positive electrode current collector 34 and / or the negative electrode current collector 32 may also be a coated foil, for example, one side (e.g., the first side or the second side) of the current collector 32, 34 includes a metal (e.g., a first metal), and the other side (e.g., the other side of the first side or the second side) of the current collector 32, 34 includes another metal (e.g., a second metal). The coated foil may include (e.g., only include) aluminum-copper (Al-Cu), nickel-copper (Ni-Cu), stainless steel-copper (SS-Cu), aluminum-nickel (Al-Ni), aluminum-stainless steel (Al-SS), and nickel-stainless steel (Ni-SS). In some variations, the positive electrode current collector 34 and / or the negative electrode current collector 32 may be pre-coated, such as a graphene or carbon-coated aluminum current collector. In certain aspects, the positive electrode current collector 34 and / or the negative electrode current collector 32 may be in the form of a foil, a slotted mesh, and / or a woven mesh.
[0178] D. Electrolyte layer
[0179] like Figure 2A and 2B As shown in FIG. 1 , an electrolyte layer 26 including a polymer gel electrolyte 30 described herein may be disposed within the battery 20 between the negative electrode 22 and the positive electrode 24. Figure 2A , the polymer gel electrolyte 30 may be present within the voids of the separator 38 and between the negative electrode electroactive particles 33 and / or the positive electrode electroactive particles 35, for example in the void spaces between the particles. Additionally or alternatively, as Figure 2B As shown in , in the battery 21, the electrolyte layer 26 may include a plurality of solid electrolyte particles 36 as described herein. For example, the solid electrolyte particles 36 may include one or more oxide-based particles, sulfide-based particles, metal-doped or alivalently substituted oxide particles, inactive oxide particles, nitride-based particles, hydride-based particles, halide-based particles, and borate-based particles, all as described herein. In such cases, the polymer gel electrolyte 30 may be present between one or more of the solid electrolyte particles 36, the negative electrode electroactive particles 33, and the positive electrode electroactive particles 35, for example, in the void space between the particles. In certain variations, the battery 20, 21 may include greater than or equal to about 0.5 wt% to less than or equal to about 50 wt%, and in certain aspects optionally greater than or equal to about 5 wt% to less than or equal to about 35 wt% of the polymer gel electrolyte 30.
[0180] Although no pores or voids appear to be left in the illustrated figure, some pores may remain between adjacent particles (including, for example, only between solid electrolyte particles 36 and / or between negative electrode electroactive particles 33 and / or between positive electrode electroactive particles 35) depending on the penetration of the polymer gel electrolyte 30. For example, the battery 20 including the polymer gel electrolyte 30 may have a porosity of less than or equal to about 50 volume percent (volume %), and in some aspects, optionally less than or equal to about 30 volume %.
[0181] E.Separator
[0182] When present, the separator 38 may comprise, for example, a microporous polymer separator containing a polyolefin or PTFE. The polyolefin may be a homopolymer (derived from a single monomer component) or a heteropolymer (derived from more than one monomer component), which may be linear or branched. If the heteropolymer is derived from two monomer components, the polyolefin may have any copolymer chain arrangement, including those of block copolymers or random copolymers. Similarly, if the polyolefin is a heteropolymer derived from more than two monomer components, it may also be a block copolymer or a random copolymer. In certain aspects, the polyolefin may be polyethylene (PE), polypropylene (PP), or a blend of PE and PP, or a multilayer structured porous membrane of PE and / or PP, such as a PP-PE double-layer structure or a PP-PE-PP three-layer structure. Commercially available polyolefin porous separators include those available from Celgard LLC. 2500 (a single-layer polypropylene divider) and 2325 (a three-layer polypropylene / polyethylene / polypropylene separator).
[0183] In some aspects, the separator 38 may further include one or more of a ceramic coating and a heat-resistant material coating. The ceramic coating and / or the heat-resistant material coating may be disposed on one or more sides of the separator 38. The material forming the ceramic layer may be selected from: alumina (Al2O3), silicon dioxide (SiO2), titanium dioxide (TiO2) and combinations thereof. The heat-resistant material may be selected from: Nomex, Aramid and combinations thereof.
[0184] When separator 38 is a microporous polymer separator, it can be a single layer or multilayer laminate, which can be manufactured by dry or wet methods. For example, in some cases, a single layer of polyolefin can form the entire separator 38. In other aspects, the separator 38 can be a fiber membrane, which has a large number of gaps extending between the relative surfaces, and can have an average thickness of, for example, less than 1 mm. However, as another example, a plurality of discrete layers of similar or dissimilar polyolefins can be assembled to form the microporous polymer separator 38. In addition to polyolefins, the separator 38 can also include other polymers, such as but not limited to polyethylene terephthalate (PET), polyvinylidene fluoride (PVDF), polyamide, polyimide, poly (amide-imide) copolymer, polyetherimide and / or cellulose, or any other material suitable for generating a desired porous structure. In some variations, the separator 38 can include a cellulose separator, a PVDF membrane and a porous polyimide membrane.
[0185] The polyolefin layer and any other optional polymer layers may be further included in the separator 38 as fiber layers to help the separator 38 have appropriate structural and porosity properties. A variety of conventionally available polymers and commercially available products are contemplated for forming the separator 38, as well as many manufacturing methods that can be used to make such microporous polymer separators 38. In certain variations, the polymer gel electrolyte can wet the separator (e.g., fill 5% to 100%, such as 90%, of the voids of the separator).
[0186] The separator 38 may also include a high temperature stable polymer, such as, but not limited to, a non-woven fabric based on polyimide nanofibers, nano-sized Al2O3 and polyethylene film coated with poly(lithium 4-styrene sulfonate), SiO2-coated polyethylene, copolyimide-coated polyethylene, polyetherimide (PEI) bisphenol-acetone diphthalic anhydride (BPADA) and p-phenylenediamine, expanded polytetrafluoroethylene reinforced polyvinylidene fluoride-hexafluoropropylene, etc. In some variations, the separator 38 may be a high temperature stable separator and include a sandwich structured PVDF / poly(m-phenylene isophthalamide) (PMIA) / PVDF nanofiber separator.
[0187] The polymer gel electrolyte can replace the liquid electrolyte in lithium ion battery cells. For example, the battery comprises a cathode layer, a silicon anode layer (e.g., columnar silicon), a separator layer between the cathode layer and the silicon anode layer, the separator layer comprising a (polymer-based) separator (see Figure 2A ), and a current collector for each of the cathode layer and the silicon anode layer. The polymer gel electrolyte may be present in all layers (eg, the cathode layer, the silicon anode layer, and the separator layer).
[0188] The polymer gel electrolyte can be used to wet the particle-particle interface in the SSB to enhance battery performance. For example, the battery may include a cathode layer, solid electrolyte particles in the cathode layer, a silicon anode layer, and a separator layer between the cathode layer and the silicon anode layer, the separator layer including solid electrolyte particles (see Figure 2B ) and an optional (polymer-based) separator, and a current collector for each of the cathode layer and the silicon anode layer. The polymer gel electrolyte may be present in all layers (e.g., the cathode layer, the silicon anode layer, and the separator layer). In certain variations, the polymer gel electrolyte may wet, for example, fill 5% to 100%, for example 80%, of the pores of the solid electrolyte layer containing the solid electrolyte particles.
[0189] Example
[0190] For example Figure 2B As shown in 0.7 Fe 0.3 PO4 and LiMn2O4 blend cathode, Li7La3Zr2O 12 (LLZO) solid electrolyte layer and silicon anode (1 mAh / cm 2 )) A soft pack battery was manufactured. The prepared polymer gel electrolyte included a combination of 95 weight percent (wt%) of 0.8 molar (mole / liter (M)) lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), 0.8 M lithium tetrafluoroborate (LiBF4) and a plasticizer + 5 wt% of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP). The details of the plasticizer are as follows:
[0191] Table 1
[0192]
[0193] The performance of soft-pack batteries at lower (e.g. -18°C) and higher temperatures (e.g. 45°C) was tested and the results showed that Figure 3-9 In. Figure 3-5 In the figure, the data points of Comparative Example 1 are represented by squares, the data points of Comparative Example 2 are represented by triangles, the data points of Example 1 are represented by circles, and the data points of Example 2 are represented by diamonds. Figure 3 In FIG. 1 , the x-axis represents the number of 45°C high temperature cycles, and the y-axis represents the capacity retention rate (%). Figure 3 As shown in Figure 1, the polymer gel electrolyte of Example 1 can achieve a satisfactory capacity retention rate. The rapid capacity decay of Comparative Example 1 may be related to the Li + Without wishing to be bound by any theory, it is believed that the solid electrolyte interface (SEI) film on silicon can be repeatedly destroyed and reformed under the influence of silicon volume expansion (greater than 300%). Figure 4 In the figure, the x-axis represents the discharge rate at 25°C (where 1 represents 1C, 2 represents 2C, 5 represents 5C, and 10 represents 10C), and the y-axis represents the capacity retention rate (%). Figure 4 As shown in , the polymer gel electrolyte of Example 1 in particular can achieve satisfactory 25°C rate performance. Figure 5 In FIG. 1 , the x-axis represents the capacity retention rate (%), and the y-axis represents the -18°C cold starting voltage (V) (voltage under a 2-second pulse) of the soft pack battery after high-temperature cycling. Figure 5 As shown in , the polymer gel electrolyte of Example 1 in particular can achieve a satisfactory -18°C discharge.
[0194] Figure 6-9 The scanning electron microscope (SEM) images of the silicon anodes of Comparative Example 1, Comparative Example 2, Example 1 and Example 2 after 100 cycles of testing at 45°C are shown. Figure 8 ) shows no obvious silicon particle breakage, indicating that a relatively robust solid electrolyte interface (SEI) is formed. Figure 6 and 7 ) shows the pulverization of silicon particles having a high fluorine content on their surface, which is suspected, without wishing to be bound by any theory, to be due to the decomposition of the gel electrolyte and the reformation of the SEI. Without wishing to be bound by any theory, it is believed that with silicon particles having a larger surface area, Example 2 ( Fig. 9 ) may provide more desirable results.
[0195] The terms "a" and "an" do not indicate a limitation of quantity, but rather indicate the presence of at least one of the referenced item. The term "or" means "and / or" unless the context clearly indicates otherwise. Reference to "aspects" throughout the specification means that a particular element (e.g., feature, structure, step, or characteristic) described in conjunction with that aspect is included in at least one aspect described herein, and may or may not be present in other aspects. Furthermore, it is to be understood that the described elements may be combined in any suitable manner in the various aspects.
[0196] When an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present.
[0197] Unless specified to the contrary herein, all test standards are the most current standards in effect as of the filing date of the present application, or, if priority is claimed, the filing date of the earliest priority application in which the test standards appear.
[0198] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.
[0199] Although the above disclosure has been described with reference to exemplary embodiments, it will be appreciated by those skilled in the art that various changes may be made and elements thereof may be replaced with equivalents without departing from the scope thereof. In addition, many modifications may be made to adapt specific circumstances or materials to the teachings of the disclosure without departing from the substantive scope of the disclosure. Therefore, it is intended that the disclosure is not limited to the specific embodiments disclosed, but will include all embodiments falling within its scope.
Claims
1. A polymer gel electrolyte for an electrochemical cell, wherein the polymer gel electrolyte comprises: Lithium salts containing sulfur and fluorine; Lithium salts containing boron; Fluorinated plasticizers; Non-fluorinated plasticizers; and Polymer body, The w / w ratio of the fluorinated plasticizer to the non-fluorinated plasticizer is from 9:1 to 1:
9. 2 . The polymer gel electrolyte of claim 1 , wherein the lithium salt containing sulfur and fluorine and the lithium salt containing boron each have a concentration of greater than or equal to about 0.6 M to less than or equal to about 2 M.
3. The polymer gel electrolyte according to claim 1, wherein: The lithium salt comprising sulfur and fluorine comprises lithium bis(trifluoromethanesulfonyl)imide (LiTFSI); The boron-containing lithium salt comprises lithium tetrafluoroborate (LiBF4); The fluorinated plasticizer comprises fluoroethylene carbonate (FEC); The non-fluorinated plasticizer comprises gamma-butyrolactone (GBL); and The polymer host includes polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
4. The polymer gel electrolyte of claim 1, wherein one or more of the following conditions are satisfied: (i) the combination of the lithium salt comprising sulfur and fluorine and the lithium salt comprising boron has a concentration of greater than or equal to about 1.2 M to less than or equal to about 4 M; (ii) the lithium salt comprising sulfur and fluorine and the lithium salt comprising boron each have a concentration of greater than or equal to about 0.6 M to less than or equal to about 2 M; (iii) a w / w ratio of the fluorinated plasticizer to the non-fluorinated plasticizer of from about 0.9:1 w / w to about 0.2:1 w / w; and (iv) the polymer host is present in an amount of 0.5 wt % to about 40 wt %.
5. The polymer gel electrolyte of claim 1, wherein one or more of the following conditions are satisfied: (i) the lithium salt comprising sulfur and fluorine comprises lithium bis(trifluoromethanesulfonyl)imide (LiTFSI); (ii) the boron-containing lithium salt comprises lithium tetrafluoroborate (LiBF4); (iii) the fluorinated plasticizer comprises fluoroethylene carbonate (FEC); (iv) the non-fluorinated plasticizer comprises gamma-butyrolactone (GBL); and (v) The polymer host comprises polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP). The polymer gel electrolyte of claim 1 , further comprising solid electrolyte particles.
7. An electrochemical cell for circulating lithium ions, the electrochemical cell comprising: a first electrode comprising a first electroactive material; a second electrode comprising a second electroactive material; and an electrolyte layer disposed between the first electrode and the second electrode, wherein at least one of the first electrode, the second electrode, and the electrolyte layer comprises a polymer gel electrolyte, the polymer gel electrolyte comprising: Lithium salts containing sulfur and fluorine; Lithium salts containing boron; Fluorinated plasticizers; Non-fluorinated plasticizers; and Polymer body.
8. The electrochemical cell of claim 7, wherein the electrolyte layer comprises: A plurality of solid electrolyte particles and the polymer gel electrolyte at least partially filling void spaces between the solid electrolyte particles.
9. The electrochemical cell of claim 7, wherein the electrolyte layer further comprises a separator, wherein the gel polymer electrolyte at least partially fills void spaces in the separator.
10. The electrochemical cell of claim 7, wherein: The lithium salt comprising sulfur and fluorine comprises lithium bis(trifluoromethanesulfonyl)imide (LiTFSI); The boron-containing lithium salt comprises lithium tetrafluoroborate (LiBF4); The fluorinated plasticizer comprises fluoroethylene carbonate (FEC); The non-fluorinated plasticizer comprises gamma-butyrolactone (GBL); and The polymer host includes polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).